Golden Ratio Proof

Prove that:

\frac { a }{ b } =\frac { a+b }{ a } =\frac { 1+\sqrt { 5 }  }{ 2 }

First say that:

p=\frac { a }{ b }

bp=a

So:

\frac { a }{ b } =\frac { a+b }{ a } \\ \\ p=\frac { bp+b }{ bp } \\ \\ p=\frac { b\left( p+1 \right)  }{ bp } \\ \\ p=\frac { p+1 }{ p } \\ \\ { p }^{ 2 }=p+1\\ \\ { p }^{ 2 }-p=1\\ \\ { \left( p-\frac { 1 }{ 2 }  \right)  }^{ 2 }-{ \left( \frac { 1 }{ 2 }  \right)  }^{ 2 }=1\\ \\ { \left( p-\frac { 1 }{ 2 }  \right)  }^{ 2 }=\frac { 4 }{ 4 } +\frac { 1 }{ 4 } \\ \\ { \left( p-\frac { 1 }{ 2 }  \right)  }^{ 2 }=\frac { 5 }{ 4 } \\ \\ p-\frac { 1 }{ 2 } =\frac { \sqrt { 5 }  }{ \sqrt { 4 }  } \\ \\ p-\frac { 1 }{ 2 } =\frac { \sqrt { 5 }  }{ 2 } \\ \\ p=\frac { 1 }{ 2 } +\frac { \sqrt { 5 }  }{ 2 } \\ \\ p=\frac { 1+\sqrt { 5 }  }{ 2 }

Now:

\frac { a+b }{ a } \\ \\ =\frac { \left( 1+\sqrt { 5 }  \right) +2 }{ \left( 1+\sqrt { 5 }  \right)  } \\ \\ =\frac { \left( 1+\sqrt { 5 }  \right)  }{ \left( 1+\sqrt { 5 }  \right)  } +\frac { 2 }{ \left( 1+\sqrt { 5 }  \right)  } \cdot \frac { \left( 1-\sqrt { 5 }  \right)  }{ \left( 1-\sqrt { 5 }  \right)  } \\ \\ =1+\frac { \left( 2-2\sqrt { 5 }  \right)  }{ -4 } \\ \\ =\frac { -4 }{ -4 } +\frac { \left( 2-2\sqrt { 5 }  \right)  }{ -4 } \\ \\ =\frac { -4+\left( 2-2\sqrt { 5 }  \right)  }{ -4 } \\ \\ =\frac { -4+2-2\sqrt { 5 }  }{ -4 } \\ \\ =\frac { -2-2\sqrt { 5 }  }{ -4 } \\ \\ =\frac { -2\left( 1+\sqrt { 5 }  \right)  }{ -2\cdot 2 } \\ \\ =\frac { 1+\sqrt { 5 }  }{ 2 }

Other posts you may be interested in...